Kebahagiaan Pada Lanjut Usia Ditinjau Dari Dukungan Keluarga - Ayu Mastuti, Dyah; , Santi Sulandari, S.Psi, .M. Ger (2016)
Abstracts Family support had a positive influence on the happiness that occur in the elderly. Someone who enters elderly, they have been experiencing impairment in the functions of cognitive, physical, and psychological. So that require attention, comfort, and affection of the family. Elderly not received get support family, in her life make elderly tend to shut off and are unhappy. Samples of this study were 100 elderly people in the village Luwang, District Gatak, Sukoharjo. The sample collection technique on this research using purposive of sampling with the characteristics of the sample as follows: a). Residing in the village Luwang, b). Staying with family (such as: parents, husband/wife, son, grandson, or brother), c). Older than 60 years. The methodology used is quantitative methods using the measure scale of happiness (Oxford Happiness Quesionnaire) and scale of support family and analysis techniques used is a correlation product moment of pearson. Based on the results obtained by analysis of the correlation coefficient (r) of 0.691and sg. (One-tailed) = 0.000, p < 0.01, meaning that there are very significant positive relationship between family support with happiness. Happiness in elderly classified as being seen from the empirical mean (RE) 99.53 and the mean hypothetical (RH) 101.5. Family support for elderly people seen quite a bit lower than the average empirical (RE) 58.73 and the mean hypothetical (RH) 78. Family support to the happiness of the elderly amounted to 48.78%, 52.22% then there are still other factors the effect on the happiness of the elderly in addition to family support factor. Key word: Family supports, happiness, elderly.